(untitled) (Journal of Association of Educational Management and Policy Practitioners, 2025)
The integration of Artificial Intelligence (AI) into Nigeria’s higher education system holds transformative potential for enhancing learning experiences, improving institutional efficiency, and addressing systemic challenges. This paper explores the future prospects of AI in Nigerian higher education by examining current trends, policy implications, and regulatory needs. AI technologies offer personalized learning experiences through adaptive systems that cater to individual student needs, thus enhancing educational outcomes. They also promise significant improvements in institutional efficiency by automating administrative tasks and optimizing resource allocation. Despite these advantages, the successful implementation of AI requires a robust policy and regulatory framework to address data privacy, ethical considerations, and equity issues. Current policies in Nigeria, while promoting digital literacy, often lack specific provisions for AI. There is a pressing need for comprehensive AI policies that ensure data protection, address algorithmic biases, and provide clear ethical guidelines for AI use. Additionally, investments in infrastructure and professional development are crucial for supporting AI integration. Equitable access to AI technologies must be prioritized to bridge the digital divide and ensure that all students benefit from AI advancements. Collaborative efforts among government agencies, educational institutions, and technology providers are essential for developing effective policies and fostering innovation. This paper concludes with recommendations for developing a dynamic regulatory framework and supporting infrastructure to harness AI’s full potential in Nigeria’s higher education sector, aiming for enhanced educational quality and equitable growth.